Pengaruh Model Pembelajaran Kooperatif dan Minat Membaca Puisi Terhadap Keterampilan Menulis Puisi - Safitri, Ruli Nur; Agustyowati, Diah Rahma Cahya; Firmani, Sakinah Isna; Sari, Ratna Intan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the interaction between the Concept Sentence type cooperative learning model and interest in reading poetry on poetry writing skills. The method used was a quasi-experiment with a population of all seventh grade students of SMP Negeri 9 and SMP Negeri 6 Purwokerto. The sample was taken using cluster simple random sampling technique. Data collection was done through tests and questionnaires. The analysis prerequisite tests include normality test (Liliefors) and homogeneity test (Bartlett). Data were analyzed using two-way ANOVA. The results showed a significant interaction between the learning model and interest in reading poetry on poetry writing skills. This is indicated by the calculated F value of 7.71, which is greater than the table F value of 3.99 at a significance level of 0.05. Thus, the cooperative learning model and interest in reading poetry together have an effect on poetry writing skills.